Age at death of major cardiovascular diseases in 13 cohorts. The seven countries study of cardiovascular diseases 45-year follow-up. Issue 1 (2nd January 2019) - Menotti, Alessandro; Puddu, Paolo Emilio; Tolonen, Hanna; Adachi, Hisashi; Kafatos, Anthony; Kromhout, Daan
Abstract: Objectives: To explore age at death (AD) for major cardiovascular diseases (CVD) and their risk factors in originally middle-aged men followed nearly to extinction in the Seven Countries Study. Materials and methods: Thirteen cohorts of men aged 40–59 years ( N  = 10, 628) in seven countries (USA, Finland, the Netherlands, Italy, Serbia, Greece, Japan) were enrolled in late 1950s and early 1960s and were followed 45 years for mortality. AD was computed for coronary heart disease (CHD), stroke (STR), heart disease of uncertain aetiology (HDUE) and for all-causes. AD was compared across CHD-HDUE-STR. Cox models were computed for each end-point using baseline age, cigarettes smoking, systolic blood pressure and serum cholesterol. Results: After 45 years 92.9% of men had died. The most common CVD death was CHD in most cohorts except some Mediterranean and Japanese cohorts where STR or HDUE were most prevalent. In 13 cohorts mean AD was 74.5, 73.5, 75.7 and 79.1 years, respectively, for all-cause, CHD, STR and HDUE mortality (all possible differences were significant). The difference, across cohorts, between the highest and the lowest mean AD was 12.9, 9.0 and 4.7 years for CHD, HDUE and STR mortality, respectively. Risk factors explored were significant predictors of all three CVD end-points, except serum cholesterol, specific to CHD mortality. Conclusions: AD is a useful indicator of previous health and aging populations. STR and HDUE are diseases appearing later in life, thus being associated with a higher AD compared with CHD mortality.